Current and Emerging Challenges in the Diseases of Trees - Bellé, Cristiano (IntechOpen, 2023)
This Edited Volume Current and Emerging Challenges in the Diseases of Trees is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Life Sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the Agricultural and Biological Sciences research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on Agricultural and Biological Sciences and open new possible research paths for further novel developments.